Processes of Resistance in Domestic Violence Offenders in Seven Sites in the United States and Canada, 2004-2005 - Levesque, Deborah ([Verlag nicht ermittelbar], 2010)
The purpose of the study was to examine the processes of resistance in domestic violence offenders. Study One (Part 1, Study One Quantitative Data) was developed to refine and offer preliminary validation of the draft processes of resistance measure. In the summer of 2004, group facilitators collected data from 346 domestic violence offenders recruited from domestic violence agencies in Florida, California, Georgia, and Rhode Island. The 88 item draft processes of resistance measure was administered as part of a 280 item paper-and-pencil survey that took approximately 60 minutes to complete. Resistance items were placed in random order in the measure and in 50 percent of the surveys, resistance items were placed in reverse order within the measure. Study Two (Part 2, Study Two Quantitative Data), administered the processes of resistance measure to a separate sample of domestic violence offenders at batterer program intake and again two months later. Participants included 358 domestic violence offenders recruited from domestic violence agencies in Florida, Virginia, Rhode Island, Michigan, and Calgary, Canada, between January and December 2005. In Study Three (Part 3, Study Three Expert Interview Qualitative Data), 16 of the 18 domestic violence experts who were interviewed in Study One during the drafting of the resistance measure were invited by telephone or email to participate in a 1- hour interview on best practices for dealing with resistance. Thirteen experts who agreed to be interviewed were mailed a list of processes of resistance measure items and asked to give recommendations on how domestic violence counselors can respond to a client engaging in those behaviors in treatment. Interviews were conducted by telephone in November 2005, with an interviewer and note taker, and audiotaped. Part 1 (Study One Quantitative Data) and Part 2 (Study Two Quantitative Data) include demographic variables such as age, race, level of education, employment and income level, relationship to the domestic assault victim, months in batterer treatment, and criminal history. Both Parts also include variables to measure stage of change, decisional balance, processes of change, self-efficacy, physical and psychological aggression, social desirability, at risk drinking, and physical and mental health. Additionally, Part 2 includes variables on program attendance and completion. Part 3 (Study Three Expert Interviews Qualitative Data) includes domestic violence experts recommendations for managing eight types of resistance in batterer treatment including system blaming, problems with partner, problems with alliance, social justification, hopelessness, isolation, psychological reactance, and passive reactance.